DDoS Attacks: Trends, Mitigation Strategies, and Future Directions - Dogra, Amit; T, Taqdir (International Journal of Computer Sciences and Engineering, 2026)
Distributed Denial of Service (DDoS) attacks pose significant threats to online services and networks by overwhelming targeted systems with malicious traffic. This paper provides a comprehensive review of DDoS attacks and explores various mitigation strategies employed by organizations to defend against these attacks. The study focuses on recent developments in attack techniques and discusses the effectiveness of different mitigation approaches. By understanding the evolving landscape of DDoS attacks and the corresponding countermeasures, organizations can enhance their resilience and minimize the impact of such attacks.